DINAMIKA POPULASI DAN STATUS STOK IKAN TEMBANG PUTIH (Escualosa thoracata) DI PERAIRAN KABUPATEN CIREBON BERDASARKAN SPAWNING POTENTIAL RATIO - Adi Spy Supriyadi; Mohammad Mukhlis Kamal; Mennofatria Boer (Politeknik Kelautan dan Perikanan Sorong, 2025)
The white sardine (Escualosa thoracata) is an essential small pelagic species supporting coastal fisheries in Java's northern waters. This study evaluated the population dynamics and stock status of the species in the coastal waters of Cirebon Regency, using the Spawning Potential Ratio (SPR) as a biological indicator. Field sampling was carried out from December 2024 to August 2025 at principal fishing grounds near the estuaries of Bungko Lor and Cisanggarung. Length–weight data, size distribution, and gonadal maturity stages were analyzed to estimate growth parameters, mortality rates, and key size indicators (Lc₅₀% and Lm₅₀%). The SPR was determined using a length-based approach. The catch was dominated by individuals measuring 66–80 mm total length (TL), with the highest frequency in the 70–74 mm TL class. The length–weight relationship followed W = 0.0000436 L2.6497 (R² = 0.8433), indicating negative allometric growth. The first capture size (Lc₅₀%) was 71.0 mm TL, slightly smaller than the size at first sexual maturity (Lm₅₀%) of 73.0 mm TL. The von Bertalanffy growth parameters were L∞ = 96.08 mm TL and K = 1.60 yr⁻¹. The exploitation rate (E) reached 0.76, exceeding the optimal level (≈ 0.5), while the SPR was 19%, below the recommended biological threshold of 20% needed to sustain recruitment. The white sardine population in Cirebon coastal waters is under heavy fishing pressure, leading to reduced reproductive potential.